Coverage of Core Mathematics Syllabus among Senior High Schools in Ghana: The Case of Sagnarigu Municipality - Nchor, Evelyn; Atepor, Stephen; Nchor, Christopher; Jonathan, Akarigo; Shila, Akamah (American Journal of Education and Practice, 2023)
As far as students' academic performance in the West Africa Secondary School Certificate Examination is concerned, coverage of syllabus among other factors has been identified as key. The purpose of the study was to investigate the perceived factors that influence core mathematics syllabus coverage in Senior High Schools in Ghana. A qualitative research approach with case study design, guided by four research questions and semi-structured oral interview guide as well as questionnaire were used in the study. Participants were selected using a purposive and convenient sampling techniques. The data was analysed in themes and presented on frequency tables. The study found that national education policies, Covid 19 pandemic, school programs, and teacher/students-related issues were the perceived factors that influenced coverage of the core mathematics syllabus. The study employed the Goal Setting and self-Efficacy theories. The instrument was pretested by the researcher to determine its validity. It was therefore recommended that government should provide schools with textbooks, furniture, teaching and learning materials, more classrooms, library, laboratories as well as motivate teachers with better conditions of service.